Evaluation of Hygiene and Sanitation Implementation in the Kitchen Area of Porto Kopi Denpasar, Bali - Sanjaya, Kadek Candra; Raditya, I Putu Tiana; Putri, Ida Ayu Karina (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2026)
The food and beverage industry demands consistent hygiene and sanitation implementation to ensure food safety and protect consumer health. This study aims to evaluate the implementation of hygiene and sanitation in the kitchen area of Porto Kopi Denpasar, Bali; identify the inhibiting factors; and describe efforts to improve compliance. A qualitative descriptive method was employed, with data collected through direct observation using a checklist instrument, an in-depth interview with the Head Kitchen, and documentation during January–May 2025. The results show that hygiene and sanitation practices at Porto Kopi Renon have been implemented in line with the established SOP, including mandatory handwashing with antiseptic before work, use of personal protective equipment (apron and gloves), three-stage dishwashing procedure, FIFO-based ingredient storage, and closed waste bins. However, deviations were found: some staff did not use head coverings, certain kitchen areas remained unclean, and cross-contamination prevention between raw and cooked ingredients was not fully applied. The main challenges identified include uneven staff understanding of hygiene and sanitation standards, inconsistent use of personal protective equipment, and insufficient attention to ingredient separation. Improvement efforts proposed include targeted training programs for staff, periodic supervisory monitoring, SOP revision and reinforcement, and facility enhancement. This study concludes that while basic hygiene and sanitation practices are in place, consistent supervision and staff capacity-building are essential to achieve optimal food safety standards.